NEW FINDINGS OF ARABIC INSCRIPTIONS OF THE 11–18TH CENTURIES IN THE VILLAGES OF AKHTYNSKY DISTRICT OF DAGESTAN - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2022)
The paper analyses some of the recent finds of Arabic-language epigraphic monuments, discovered by the author in Akhtynsky district of Dagestan during the field work, aimed at studying the epigraphic heritage. The inscriptions were revealed in different settlements, including abandoned villages in remote mountainous areas. In terms of genre, the epigraphic monuments under review can be attributed to constructional, possessory, good-wishing inscriptions, epitaphs and excerpts from Quran. Chronologically the inscriptions cover the period from the 11th century up to the end of the 18th century. Some of the inscriptions are dated; to determine the time of writing of undated inscriptions, we applied dating by paleographic features of writing. The earliest inscriptions are written in Arabic “Kufi” script. Kufic inscriptions were first revealed in highland Lezgin villages of Maza and Gdym. The discovery of Kufic inscriptions in the village of Maza confirm the information from written sources that this village has centuries-old history. Therefore, the information about the early history of Maza, which is set out in the historical work Ta’rikh Maza, should be recognized as real. The previously unknown Kufic inscription of the 12–13th centuries, revealed in the ancient village of Khnow, is a fine example of medieval Arabic calligraphy. Of great interest is the epitaph of 1468-69 preserved in the sanctuary of the village Lutkun, where the date is indicated with numbers; this fact is rarely found in medieval inscriptions of Dagestan. Some suggest that one of the eponyms of the sanctuary was a Muslim activist of the 15th century. The inscriptions of the 18th century from the villages of Yalak, Yaltsug and Khkem inform about the construction of bridges and a mausoleum, and the possessory inscriptions of the 18th century from the villages of Yalak and Khrug were made in connection with the construction of private residential buildings.
Keywords: Arabic epigraphy; Dagestan; Akhtynsky district; 11-18th centuries; Kufic inscriptions